Vehicle Motion Model with Wheel Lock - Xaydarali Fayzullayev (Genius Journals, 2022)
This article examines the braking process of cars. Based on the work of researchers V. G. Wilke and I. L. Shapovalov, we considered the model of car movement with locked wheels. In this article, we compared the results of scientists' research on wheel blacking
Keywords: Car; brake; wheel; mass